Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Matra Adhiraya Nusantara Jakarta Barat - Jamaludin, Pusporini Palupi; Komala, Laura; Paringsih, Paringsih (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The aim of this research is to determine the influence of Leadership Style and Work Discipline on employee performance at PT Matra Adhiraya Nusantara West Jakarta. The research method used is a quantitative method. The data collection techniques in this research include distributing questionnaires to all employees and the data analysis techniques used in this research are validity test, reliability test, classical assumption test, descriptive analysis, simple linear regression analysis, multiple linear regression analysis and partial hypothesis testing ( t) and simultaneous (F). The results of the research show that leadership style and work discipline influence employee performance with a regression equation of Y = 2.020 + 0.618 X1 + 0.339 > t table or 7.239>1.993 then Ho1 is rejected and Ha1 is accepted. Partially, Work Discipline influences employee performance with the results of the t test > t table or 4.098> 1.993, so Ho2 is rejected and Ha2 is accepted. The results of simultaneous hypothesis testing show that the calculated f value is > f table or 166.099 > 3.120, so Ho3 is rejected and Ha3 is accepted. It can be concluded that the research results show that Leadership Style and Work Discipline influence employee performance at PT Matra Adhiraya Nusantara, West Jakarta.